1999
DOI: 10.1093/jee/92.4.759
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophobic Particle Films: A New Paradigm for Suppression of Arthropod Pests and Plant Diseases

Abstract: We introduce a unique concept, hydrophobic particle film technology, that represents the combined synthesis of knowledge on the use of hydrophobic films, physical particle barriers, and white reflective surfaces to suppress arthropod pests and diseases of agricultural crops. The hydrophobic particle film is based on the inert mineral, kaolin, that is surface treated with a water-repelling agent. We demonstrate suppression of important tree fruit arthropod pests and diseases by altering the plants surface with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
218
4
17

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 266 publications
(256 citation statements)
references
References 33 publications
(36 reference statements)
17
218
4
17
Order By: Relevance
“…2a and 2b). This product appears to be effective against other dipteran pests (Mazor & Erez, 2004;Leskey et al, 2010;Pascual et al, 2010), and several authors have reported that kaolin forms a barrier when applied on fruits, hindering visual and tactile recognition and thus preventing oviposition (Glenn et al, 1999;Bürgel et al, 2005). The results obtained here suggest that this is not the case with SWD and the coating formed by kaolin on blueberries did not affect the oviposition process and thus did not prevent egg laying.…”
Section: Acknowledgementsmentioning
confidence: 99%
“…2a and 2b). This product appears to be effective against other dipteran pests (Mazor & Erez, 2004;Leskey et al, 2010;Pascual et al, 2010), and several authors have reported that kaolin forms a barrier when applied on fruits, hindering visual and tactile recognition and thus preventing oviposition (Glenn et al, 1999;Bürgel et al, 2005). The results obtained here suggest that this is not the case with SWD and the coating formed by kaolin on blueberries did not affect the oviposition process and thus did not prevent egg laying.…”
Section: Acknowledgementsmentioning
confidence: 99%
“…In addition, it has been referred as effective in the control of some plant pests such as aphids (COTTRELL et al, 2002), olive fruit flies (SAOUR & MAKEE, 2004) and pear psyllids (GLENN et al, 1999). Thus, the efficiency of kaolin (with or without neem oil), compared with diatomaceous earth, on Z. subfasciatus in common beans was studied in laboratory.…”
Section: Introductionmentioning
confidence: 99%
“…Elma ve armutlarda yapılan çalışmalarda kaolinin armut psillidi (Cacopsylla prycola)'nin yumurta ve erginleri üzerine etkili olduğu ve bu etkinin istatistik olarak kontrol grubundan farklılık gösterdiği saptanmıştır [23]. Aynı araştırıcılar ikinoktalı kırmızıörümcek (T. urticae) ve turunçgil yeşil yaprakbiti (Aphis spiraecola) ile de yaptıkları çalışmalarda benzer sonuçları bulmuşlardır.…”
Section: Tartışma Ve Sonuçunclassified